2016
DOI: 10.1007/s12035-016-9925-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-338 Attenuates Cortical Neuronal Outgrowth by Modulating the Expression of Axon Guidance Genes

Abstract: MicroRNAs (miRs) are small non-coding RNAs that confer robustness to gene networks through post-transcriptional gene regulation. Previously, we identified miR-338 as a modulator of axonal outgrowth in sympathetic neurons. In the current study, we examined the role of miR-338 in the development of cortical neurons and uncovered its downstream mRNA targets. Long-term inhibition of miR-338 during neuronal differentiation resulted in reduced dendritic complexity and altered dendritic spine morphology. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
(64 reference statements)
2
15
0
Order By: Relevance
“…1E findings that miR-338 sponge efficiently reduces endogenous miR-338 levels in cortical neurons. 18 In vivo modulation of miR-338 levels affects neuronal migration in the developing cortex Since previous studies suggested that miR-338 might have the capacity to modulate axonal development in neurons, we aimed at determining the effects of miR-338 expression changes on cortical development. To examine the expression profile of miR-338 during brain development, total RNA was isolated from brain tissue obtained at several developmental time points, namely, embryonic (E) day E10.5, E13.5, E14.5, E15.5, E16.5, E18.5, and at postnatal day (P) 0, followed by qRT-PCR quantification of mature miR-338 levels at these time points.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1E findings that miR-338 sponge efficiently reduces endogenous miR-338 levels in cortical neurons. 18 In vivo modulation of miR-338 levels affects neuronal migration in the developing cortex Since previous studies suggested that miR-338 might have the capacity to modulate axonal development in neurons, we aimed at determining the effects of miR-338 expression changes on cortical development. To examine the expression profile of miR-338 during brain development, total RNA was isolated from brain tissue obtained at several developmental time points, namely, embryonic (E) day E10.5, E13.5, E14.5, E15.5, E16.5, E18.5, and at postnatal day (P) 0, followed by qRT-PCR quantification of mature miR-338 levels at these time points.…”
Section: Resultsmentioning
confidence: 99%
“…miR-338 target analysis in primary cortical neurons raised the possibility that miR-338 could similarly modulate the expression of many genes fitting in pathways critical for programming neuronal development. 18 Previously we have used anti-miR-338 with a relatively short half-life, and provided evidence that this miR attenuates neuronal outgrowth by locally regulating axonal mitochondrial function. 17 Our studies suggested that the repressing effect of miR-338 on axonal outgrowth diminished over time as axonal outgrowth grew near the length of unaltered control neurons within 5-6 d (unpublished observation).…”
Section: Mir-338 Affects Neuronal Morphologies and Polarity In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…Since pain and morphine tolerance have similar signalling pathways, miRNA may also be involved in the development of morphine tolerance, and neurons in the dorsal horn of the spinal cord may also be key in pain conduction and development of morphine tolerance [23]. While miR-338 is a kind of brain-specific miRNA [10] also expressed in spinal cord [24], it is safe to infer that miR-338 is related to development of morphine tolerance. Researches show that miR-338 expression was down-regulated in liver cancer and oral squamous cell carcinoma, and this reduced level of miR-338 was closely related to malignant activities like cancer metastasis that can cause BCP [2527]; thus we can infer that miR-338 expression may also be down-regulated.…”
Section: Discussionmentioning
confidence: 99%